Domination of Tradition in Under Age Marriage - Sulaiman Sulaiman (Balai Penelitian dan Pengembangan Agama Semarang, 2012)
The focus of this research was the phenomenon of early marriage which was domi- nated by cultural traditions. It was a qualitative research that used interview, obser- vation and document reviews to collect the data. The result of the study was expected to provide people enough information and materials on the picture of early marriage. The findings showed some determining factors in the phenomenon: culture, textual understanding of religion, and economic motives. Although the phenomenon of early marriage was like this, people actually perceive that the ideal marriage was a mar- riage which is conducted after reaching the age mature enough to be able to live inde- pendently. The practice of such marriage should get special attention because there are many social problems that are related direcly to the mature age of marriage, such as: mortality, poverty, and the low quality of education. Therefore, the implementa- tion of the marriage must be in accordance with the laws and regulations.